Report of Exosomes Isolated from a Human Uterine Leiomyoma Cell Line and Their Impact on Endometrial Vascular Endothelial Cells - Antonia Navarro; Maria Victoria Bariani; Hang-Soo Park; Ami R. Zota; Ayman Al-Hendy (MDPI AG, 2022)
Uterine leiomyomas are the most common pelvic tumor in women of reproductive age; they cause irregular heavy menstrual bleeding leading to anemia and subsequent negative effects on quality of life. Exosomes have arisen as main players of disease progression in several illnesses, including a range of benign and malignant conditions; however, their role in leiomyomas' pathophysiology remains unknown. We investigated the effect of exosomes derived from human uterine leiomyoma tumor cells (HULM) and human myometrial cells (UTSM) on the behavior of human endometrial microvascular endothelial cells (HEMEC). HULM- and UTSM-derived exosomes were isolated and cocultured with HEMECs. Then, cell proliferation, mRNA expression, tube formation assay, and RNA-seq were performed. Treatment of HEMEC with HULM-derived exosomes increased cell proliferation by 60% compared to control untreated cells, upregulated C-MYC and VEGFA expression levels, and increased tube formation, length, and branching (markers of angiogenesis). Profiling of miRNA revealed that 84 miRNAs were significantly downregulated and 71 were upregulated in HULM-derived exosomes compared to UTSM-derived exosomes. These findings suggest that HULM-derived exosomes might have effects on HEMEC function, containing factors that enhance endometrial proliferation and angiogenesis, which may contribute to heavy menstrual bleeding. Further research on exosomes in uterine leiomyoma may identify possible novel biomarkers for treatment.